PERAN PENDAMPING DALAM MEMBERIKAN DUKUNGAN PADA KORBAN KEKERASAN SEKSUAL PADA REMAJA: The Role of Counselors in Providing Support to Adolescent Juvenile Victims of Sexual Violence - Tertulus Daeng Patta; Devi Novita Sheldena; Fredericksen Victoranto Amseke (Yayasan Al-Amin Qalbu, 2026)
The problem of sexual violence in South Central Timor Regency shows a significant increase from year to year, with data from the UPTD PPA DP3A recording more than 200 cases between 2019 and 2024. This phenomenon has a serious impact on the physical and psychological condition of victims. In this situation, the role of companions is crucial in providing comprehensive support so that victims can recover emotionally, socially, and spiritually. The purpose of this study is to determine the role of companions in providing support to victims of sexual violence at the UPTD PPA DP3A of South Central Timor Regency, as well as to analyze the form of support provided and the factors that influence its success. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that companions carry out four main functions: providing emotional support to help victims deal with trauma, legal support in the investigation and protection process, psychological and pastoral support through individual counseling, and social and economic support during the reintegration stage of victims into the community. The conclusion of this study confirms that the role of counselors has an important contribution to the recovery process of victims of sexual violence, not only from a psychological and social aspect, but also in restoring the victim's faith and self-esteem